Local immune response to larvae of Rhipicephalus microplus in Santa Gertrudis cattle. (15th February 2018) - Constantinoiu, C. C.; Lew‐Tabor, A.; Jackson, L. A.; Jorgensen, W. K.; Piper, E. K.; Mayer, D. G.; Johnson, L.; Venus, B.; Jonsson, N. N.
Summary: This study investigated the local immune response at larval attachment sites in Santa Gertrudis cattle with low and high levels of tick resistance. Skin samples with tick larvae attached were collected from Santa Gertrudis cattle at the end of a period of 25 weekly infestations, when the animals manifested highly divergent tick‐resistant phenotypes. There was a tendency for more CD3 +, CD4 +, CD8 +, CD25 +, γδ T cells and neutrophils to concentrate at larval tick attachment site in susceptible cattle than in resistant cattle but the differences were significant only for γδ T cells and CD4 + cells. Most of the cattle developed intra‐epidermal vesicles at the larval attachment site but the predominant cell within or around the vesicles was the neutrophil in susceptible animals and eosinophil in the resistant animals. The monoclonal antibodies (mAbs) specific for CD45 and CD45 RO antigens reacted with skin leucocytes from a higher number of susceptible cattle than resistant cattle. Our data suggest that some of the cellular responses mounted at larval attachment site are not involved in tick protection. The mAbs specific for CD45 and CD45 RO directly, or a test for CD45 genotype might be developed as markers of tick susceptibility or resistance.